Benefit of a wearable cardioverter defibrillator for detection and therapy of arrhythmias in patients with myocarditis. (22nd April 2021) - Tscholl, Verena; Wielander, Dennis; Kelch, Felicitas; Stroux, Andrea; Attanasio, Philipp; Tschöpe, Carsten; Landmesser, Ulf; Roser, Mattias; Huemer, Martin; Heidecker, Bettina; Nagel, Patrick
Abstract: Aims: Myocarditis may lead to malignant arrhythmias and sudden cardiac death. As of today, there are no reliable predictors to identify individuals at risk for these catastrophic events. The aim of this study was to evaluate if a wearable cardioverter defibrillator (WCD) may detect and treat such arrhythmias adequately in the peracute setting of myocarditis. Methods and results: In this observational, retrospective, single centre study, we reviewed patients presenting to the Charité Hospital from 2009 to 2017, who were provided with a WCD for the diagnosis of myocarditis with reduced ejection fraction (<50%) and/or arrhythmias. Amongst 259 patients receiving a WCD, 59 patients (23%) were diagnosed with myocarditis by histology. The mean age was 46 ± 14 years, and 11 patients were women (19%). The mean WCD wearing time was 86 ± 63 days, and the mean daily use was 20 ± 5 h. During that time, two patients (3%) had episodes of sustained ventricular tachycardia (VT; four total) corresponding to a rate of 28 sustained VT episodes per 100 patient‐years. Consequently, one of these patients underwent rhythm stabilization through intravenous amiodarone, while the other patient received an implantable cardioverter defibrillator. Two patients (3.4%) were found to have non‐sustained VT. Conclusions: Using a WCD after acute myocarditis led to the detection of sustained VT in 2/59 patients (3%). While a WCD may prevent sudden cardiac death after myocarditis, our data suggest that WCD may have impact on clinical management through monitoring and arrhythmia detection.